Santana Pérez, Juan Manuel and Germán Santana Pérez. Doors to the sea. Atlantic African Isles in the old regime. Valencia: Tirant lo Blanch, 373 pp. - Hernández Suárez, Sergio (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Reseña al libro Santana Pérez, Juan Manuel y Germán Santana Pérez. Puertas en el mar. Islas Africanas Atlánticas en el antiguo régimen. Valencia: Tirant lo Blanch, 373 pp.